40Ar/39Ar dating results from the Shijiatun Formation, Jiaolai Basin: New age constraints on the Cretaceous terrestrial volcanic-sedimentary sequence of China. (June 2018) - Li, Youjuan; He, Huaiyu; Deng, Chenglong; Pan, Yongxin; Ji, Qiang; Wang, Chengshan; Zheng, Dewen; Zhu, Rixiang
Abstract: We provide a stringent age constraint on the Upper Cretaceous terrestrial strata based on 40 Ar/ 39 Ar dating of a continuous volcanic-sedimentary sequence drilled from Jiaolai Basin in Shandong Province, eastern China. The volcanic-sedimentary sequence, which is mainly composed of basaltic rocks interbedded with thin-bedded siltstone and fine sandstone, comprises the depth interval from 614 to 769 m of the Cretaceous Continental Scientific Drilling borehole (CCSD-LK-I), and belongs to Member S5 of the Shijiatun Formation by lithostratigraphic division. 40 Ar/ 39 Ar dating of the basalts from CCSD-LK-I yielded a latest age of 73.5 ± 1.1 Ma at 614 m depth and a basal age of 79.7 ± 2.7 Ma at 757 m depth, corresponding to Campanian in age. Magnetostratigraphy revealed a correlation with the geomagnetic polarity time scale from lower Chron C33n to lower Chron C32n.2n, further demonstrating that the terrestrial volcanic-sedimentary sequence of the Shijiatun Formation is of middle-late Campanian age. The established chronological framework allows the interregional correlation of Member S5 of the Shijiatun Formation in Jiaolai Basin to the strata from other basins in northeastern China, northwestern China and central-southern China. In addition, the 40 Ar/ 39 Ar age of 73.5 ± 1.1 Ma from the topmost basalt of the Shijiatun Formation indicates that the age of the overlying Jiaozhou Formation is younger than Campanian, and it also supports the location of the K/Pg boundary within the depth interval of 450–520 m in borehole CCSD-LK-I.